MEDICINAL MUSHROOM BIOACTIVES: POTENTIAL SOURCES FOR ANTI-CANCER DRUG DEVELOPMENT - JANARDHANAN, KAINOOR K.; RAVIKUMAR, KORATTUVALAPPIL S.; KARUPPAYIL, S. MOHAN (International Journal of Applied Pharmaceutics, 2020)
Mushrooms represent a major yet largely untapped source of therapeutically useful bioactive compounds. Despite mushrooms were in use since antiquity in traditional folk medicine attempts to isolate their bioactive components and to elucidate their medicinal properties have started only recently. Many pharmaceutical substances with unique properties were recently extracted from mushrooms and made their way all over the world. A number of medicinal mushrooms have been identified to possess anticancer effects recently. Some of the well-known examples are Lentinan from Lentinus edodes, Krestin from Trametes versicolor, Ganopoly from Ganoderma lucidum and Schizophyllan from Schizophyllum commune. We investigated the anticancer activities of a number of medicinal mushrooms in our laboratory. Some of the recent scientific evdences on the anticancer activities of Ganoderma lucidum, Phellinus rimosus, and Fomitopsis pinicola are discussed in this short review.